Central nervous system relapse of primary cutaneous anaplastic large cell lymphoma: A case report - Satoshi Mitsuyuki; Sayaka Okazaki; Satoru Mukai; Ai Matsuura; Yumiko Yasuhara; Aya Tanaka; Koichi Oshima; Kazuo Hatanaka (eJHaem)
Abstract Primary cutaneous anaplastic large cell lymphoma (PC‐ALCL) has a high relapse rate. However, it typically remains confined to the skin and has a favorable long‐term prognosis. We describe a case of PC‐ALCL that experienced a relapse in the central nervous system (CNS). The patient presented with somatosensory abnormalities in the extremities after local treatment of skin lesions and was diagnosed with CNS relapse of PC‐ALCL. Methotrexate, procarbazine, and vincristine therapy, and alternating brentuximab vedotin, followed by autologous hematopoietic stem cell transplantation (ASCT) cured the CNS lesions, whereas the skin lesions relapsed early. PC‐ALCL could relapse in the CNS; systemic chemotherapy and ASCT may be effective.